1953
DOI: 10.3733/hilg.v22n06p179
|View full text |Cite
|
Sign up to set email alerts
|

Carotene and protein contents of alfalfa as influenced by variety and certain environmental factors

Abstract: ALFALFA has long been of prime importance as a hay and forage crop because of its high protein and carotene contents. Protein is generally stable during storage, but may be lost in leaf shatter through poor management in handling the crop. Carotene, on the other hand, is very unstable and losses may be severe during harvest operations and storage. In spite of customary large losses of carotene, alfalfa products are of great importance in the feeding of livestock and poultry because of their content of beta-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…\8) and Jones et dl. (5) found that there were siinificanr differences in protein content between certain alfalfa varieties.…”
Section: Introductionmentioning
confidence: 99%